Nosocomial outbreak of Enteroccocus gallinarum: untaming of rare species of enterococci (2008)
An unusual increase in infections caused by vancomycin-resistant Enterococcus gallinarum (VREG) was identified in May 2004, in a Colombian tertiary care teaching hospital. A case-control study was subsequently designed to identify risk factors associated with the development of infections due to these organisms. All VREG isolates were subjected to antimicrobial susceptibility testing, vancomycin resistance gene detection and pulsed-field gel electrophoresis (PFGE) typing. Additionally, the presence of genes associated with an acquired pathogenicity island of E. faecalis and a hyl-like gene of E. faecium was assessed by hybridisation assays. Eleven cases of VREG were identified between May through June 2004. VREG was isolated from blood (N=4), surgical secretions (N=4), paranasal sinus secretion (N=1), lung abscess (N=1) and urine (N=1). Infections with VREG were associated with mucositis, hospitalisation in the haematology ward and surgical unit, length of hospital stay prior to culture and invasive procedures within 30 days prior to the culture. Logistic regression found that female sex and hospitalisation in the surgical unit were independent factors for VREG infection. All isolates were identified as E. gallinarum, harboured the vanC1 gene and exhibited indistinguishable restriction patterns by PFGE. Virulence-associated genes were not detected. This is the first documented hospital-wide outbreak of VREG and highlights the fact that uncommon species of enterococci are capable of nosocomial dissemination.